P. 1
Integral Table

Integral Table

|Views: 2|Likes:
Published by Hoang Giang
Common integral differential tabal
Common integral differential tabal

More info:

Categories:Types, School Work
Published by: Hoang Giang on May 01, 2013
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

02/17/2015

pdf

text

original

Table of Integrals


Basic Forms
_
x
n
dx =
1
n + 1
x
n+1
+ c (1)
_
1
x
dx = lnx + c (2)
_
udv = uv −
_
vdu (3)
_
1
ax + b
dx =
1
a
ln|ax + b| + c (4)
Integrals of Rational Functions
_
1
(x + a)
2
dx = −
1
x + a
+ c (5)
_
(x + a)
n
dx =
(x + a)
n+1
n + 1
+ c, n = −1 (6)
_
x(x + a)
n
dx =
(x + a)
n+1
((n + 1)x −a)
(n + 1)(n + 2)
+ c (7)
_
1
1 + x
2
dx = tan
−1
x + c (8)
_
1
a
2
+ x
2
dx =
1
a
tan
−1
x
a
+ c (9)
_
x
a
2
+ x
2
dx =
1
2
ln|a
2
+ x
2
| + c (10)
_
x
2
a
2
+ x
2
dx = x −a tan
−1
x
a
+ c (11)
_
x
3
a
2
+ x
2
dx =
1
2
x
2

1
2
a
2
ln|a
2
+ x
2
| + c (12)
_
1
ax
2
+ bx + c
dx =
2

4ac −b
2
tan
−1
2ax + b

4ac −b
2
+ C (13)
_
1
(x + a)(x + b)
dx =
1
b −a
ln
a + x
b + x
, a = b (14)
_
x
(x + a)
2
dx =
a
a + x
+ ln|a + x| + C (15)
_
x
ax
2
+ bx + c
dx =
1
2a
ln|ax
2
+ bx + c|

b
a

4ac −b
2
tan
−1
2ax + b

4ac −b
2
+ C (16)
Integrals with Roots
_

x −adx =
2
3
(x −a)
3/2
+ C (17)
_
1

x ±a
dx = 2

x ±a + C (18)
_
1

a −x
dx = 2

a −x + C (19)
_
x

x −adx =
2
3
a(x −a)
3/2
+
2
5
(x −a)
5/2
+ C (20)
_

ax + bdx =
_
2b
3a
+
2x
3
_

ax + b + C (21)
_
(ax + b)
3/2
dx =
2
5a
(ax + b)
5/2
+ C (22)
_
x

x ±a
dx =
2
3
(x ±2a)

x ±a + C (23)
_ _
x
a −x
dx = −
_
x(a −x)
−a tan
−1
_
x(a −x)
x −a
+ C (24)
_ _
x
a + x
dx =
_
x(a + x)
−a ln
_√
x +

x + a
¸
+ C (25)
_
x

ax + bdx =
2
15a
2
(−2b
2
+ abx + 3a
2
x
2
)

ax + b + C (26)
_
_
x(ax + b)dx =
1
4a
3/2
_
(2ax + b)
_
ax(ax + b)
−b
2
ln
¸
¸
¸a

x +
_
a(ax + b)
¸
¸
¸
_
+ C (27)
_
_
x
3
(ax + b)dx =
_
b
12a

b
2
8a
2
x
+
x
3
_
_
x
3
(ax + b)
+
b
3
8a
5/2
ln
¸
¸
¸a

x +
_
a(ax + b)
¸
¸
¸ + C (28)

c 2007. From http://integral-table.com, last revised December 6, 2007. This material is provided as is without warranty or representation
about the accuracy, correctness or suitability of this material for any purpose. Some restrictions on use and distribution may apply, including the
terms of the Creative Commons Attribution-Noncommercial-Share Alike 3.0 Unported License. See the web site for details. The formula numbers
on this document may be different from the formula numbers on the web page.
1
_
_
x
2
±a
2
dx =
1
2
x
_
x
2
±a
2
±
1
2
a
2
ln
¸
¸
¸x +
_
x
2
±a
2
¸
¸
¸ + C (29)
_
_
a
2
−x
2
dx =
1
2
x
_
a
2
−x
2
+
1
2
a
2
tan
−1
x

a
2
−x
2
+ C (30)
_
x
_
x
2
±a
2
dx =
1
3
_
x
2
±a
2
_
3/2
+ C (31)
_
1

x
2
±a
2
dx = ln
¸
¸
¸x +
_
x
2
±a
2
¸
¸
¸ + C (32)
_
1

a
2
−x
2
dx = sin
−1
x
a
+ C (33)
_
x

x
2
±a
2
dx =
_
x
2
±a
2
+ C (34)
_
x

a
2
−x
2
dx = −
_
a
2
−x
2
+ C (35)
_
x
2

x
2
±a
2
dx =
1
2
x
_
x
2
±a
2

1
2
a
2
ln
¸
¸
¸x +
_
x
2
±a
2
¸
¸
¸ + C (36)
_
_
ax
2
+ bx + cdx =
b + 2ax
4a
_
ax
2
+ bx + c
+
4ac −b
2
8a
3/2
ln
¸
¸
¸2ax + b + 2
_
a(ax
2
+ bx
+
c)
¸
¸
¸ + C (37)
_
x
_
ax
2
+ bx + c =
1
48a
5/2
_
2

a
_
ax
2
+ bx + c

_
3b
2
+ 2abx + 8a(c + ax
2
)
_
+3(b
3
−4abc) ln
¸
¸
¸b + 2ax + 2

a
_
ax
2
+ bx + x
¸
¸
¸
_
(38)
_
1

ax
2
+ bx + c
dx =
1

a
ln
¸
¸
¸2ax + b + 2
_
a(ax
2
+ bx + c)
¸
¸
¸ + C (39)
_
x

ax
2
+ bx + c
dx =
1
a
_
ax
2
+ bx + c
+
b
2a
3/2
ln
¸
¸
¸2ax + b + 2
_
a(ax
2
+ bx + c)
¸
¸
¸ + C (40)
Integrals with Logarithms
_
lnaxdx = xlnax −x + C (41)
_
lnax
x
dx =
1
2
(lnax)
2
+ C (42)
_
ln(ax + b)dx =
_
x +
b
a
_
ln(ax + b) −x + C, a = 0 (43)
_
ln
_
a
2
x
2
±b
2
_
dx = xln
_
a
2
x
2
±b
2
_
+
2b
a
tan
−1
ax
b
−2x + C (44)
_
ln
_
a
2
−b
2
x
2
_
dx = xln
_
ar −b
2
x
2
_
+
2a
b
tan
−1
bx
a
−2x + C (45)
_
ln
_
ax
2
+ bx + c
_
dx =
1
a
_
4ac −b
2
tan
−1
2ax + b

4ac −b
2
−2x +
_
b
2a
+ x
_
ln
_
ax
2
+ bx + c
_
+ C (46)
_
xln(ax + b)dx =
bx
2a

1
4
x
2
+
1
2
_
x
2

b
2
a
2
_
ln(ax + b) + C (47)
_
xln
_
a
2
−b
2
x
2
_
dx = −
1
2
x
2
+
1
2
_
x
2

a
2
b
2
_
ln
_
a
2
−b
2
x
2
_
+ C (48)
Integrals with Exponentials
_
e
ax
dx =
1
a
e
ax
+ C (49)
_

xe
ax
dx =
1
a

xe
ax
+
i

π
2a
3/2
erf
_
i

ax
_
+ C,
where erf(x) =
2

π
_
x
0
e
−t
2
dtet (50)
_
xe
x
dx = (x −1)e
x
+ C (51)
_
xe
ax
dx =
_
x
a

1
a
2
_
e
ax
+ C (52)
_
x
2
e
x
dx =
_
x
2
−2x + 2
_
e
x
+ C (53)
2
_
x
2
e
ax
dx =
_
x
2
a

2x
a
2
+
2
a
3
_
e
ax
+ C (54)
_
x
3
e
x
dx =
_
x
3
−3x
2
+ 6x −6
_
e
x
+ C (55)
_
x
n
e
ax
dx = (−1)
n
1
a
Γ[1 + n, −ax],
where Γ(a, x) =
_

x
t
a−1
e
−t
dt (56)
_
e
ax
2
dx = −
i

π
2

a
erf
_
ix

a
_
(57)
Integrals with Trigonometric Functions
_
sinaxdx = −
1
a
cos ax + C (58)
_
sin
2
axdx =
x
2

sin2ax
4a
+ C (59)
_
sin
n
axdx =

1
a
cos ax
2
F
1
_
1
2
,
1 −n
2
,
3
2
, cos
2
ax
_
+ C (60)
_
sin
3
axdx = −
3 cos ax
4a
+
cos 3ax
12a
+ C (61)
_
cos axdx =
1
a
sinax + C (62)
_
cos
2
axdx =
x
2
+
sin2ax
4a
+ C (63)
_
cos
p
axdx = −
1
a(1 + p)
cos
1+p
ax×
2
F
1
_
1 + p
2
,
1
2
,
3 + p
2
, cos
2
ax
_
+ C (64)
_
cos
3
axdx =
3 sinax
4a
+
sin3ax
12a
+ C (65)
_
cos axsinbxdx =
cos[(a −b)x]
2(a −b)

cos[(a + b)x]
2(a + b)
+ C, a = b (66)
_
sin
2
axcos bxdx = −
sin[(2a −b)x]
4(2a −b)
+
sinbx
2b

sin[(2a + b)x]
4(2a + b)
+ C (67)
_
sin
2
xcos xdx =
1
3
sin
3
x + C (68)
_
cos
2
axsinbxdx =
cos[(2a −b)x]
4(2a −b)

cos bx
2b

cos[(2a + b)x]
4(2a + b)
+ C (69)
_
cos
2
axsinaxdx = −
1
3a
cos
3
ax + C (70)
_
sin
2
axcos
2
bxdx =
x
4

sin2ax
8a

sin[2(a −b)x]
16(a −b)
+
sin2bx
8b

sin[2(a + b)x]
16(a + b)
+ C (71)
_
sin
2
axcos
2
axdx =
x
8

sin4ax
32a
+ C (72)
_
tanaxdx = −
1
a
lncos ax + C (73)
_
tan
2
axdx = −x +
1
a
tanax + C (74)
_
tan
n
axdx =
tan
n+1
ax
a(1 + n)
×
2
F
1
_
n + 1
2
, 1,
n + 3
2
, −tan
2
ax
_
+ C (75)
_
tan
3
axdx =
1
a
lncos ax +
1
2a
sec
2
ax + C (76)
_
sec xdx = ln| sec x + tanx| + C
= 2 tanh
−1
_
tan
x
2
_
+ C (77)
_
sec
2
axdx =
1
a
tanax + C (78)
_
sec
3
xdx =
1
2
sec xtanx +
1
2
ln| sec xtanx| + C (79)
_
sec xtanxdx = sec x + C (80)
_
sec
2
xtanxdx =
1
2
sec
2
x + C (81)
_
sec
n
xtanxdx =
1
n
sec
n
x + C, n = 0 (82)
_
csc xdx = ln
¸
¸
¸tan
x
2
¸
¸
¸ + C = ln| csc x −cot x| + C (83)
3
_
csc
2
axdx = −
1
a
cot ax + C (84)
_
csc
3
xdx = −
1
2
cot xcsc x +
1
2
ln| csc x −cot x| + C (85)
_
csc
n
xcot xdx = −
1
n
csc
n
x + C, n = 0 (86)
_
sec xcsc xdx = ln| tanx| + C (87)
Products of Trigonometric Functions and Monomials
_
xcos xdx = cos x + xsinx + C (88)
_
xcos axdx =
1
a
2
cos ax +
x
a
sinax + C (89)
_
x
2
cos xdx = 2xcos x +
_
x
2
−2
_
sinx + C (90)
_
x
2
cos axdx =
2xcos ax
a
2
+
a
2
x
2
−2
a
3
sinax + C (91)
_
x
n
cosxdx = −
1
2
(i)
n+1
[Γ(n + 1, −ix)
+(−1)
n
Γ(n + 1, ix)] + C (92)
_
x
n
cosaxdx =
1
2
(ia)
1−n
[(−1)
n
Γ(n + 1, −iax)
−Γ(n + 1, ixa)] + C (93)
_
xsinxdx = −xcos x + sinx + C (94)
_
xsinaxdx = −
xcos ax
a
+
sinax
a
2
+ C (95)
_
x
2
sinxdx =
_
2 −x
2
_
cos x + 2xsinx + C (96)
_
x
2
sinaxdx =
2 −a
2
x
2
a
3
cos ax +
2xsinax
a
3
+ C (97)
_
x
n
sinxdx = −
1
2
(i)
n
[Γ(n + 1, −ix)
−(−1)
n
Γ(n + 1, −ix)] + C (98)
Products of Trigonometric Functions and
Exponentials
_
e
x
sinxdx =
1
2
e
x
(sinx −cos x) + C (99)
_
e
bx
sinaxdx =
1
a
2
+ b
2
e
bx
(b sinax −a cos bx) + C (100)
_
e
x
cos xdx =
1
2
e
x
(sinx + cos x) + C (101)
_
e
bx
cos axdx =
1
a
2
+ b
2
e
bx
(a sinax + b cos ax) + C (102)
_
xe
x
sinxdx =
1
2
e
x
(cos x −xcos x + xsinx) + C (103)
_
xe
x
cos xdx =
1
2
e
x
(xcos x −sinx + xsinx) + C (104)
Integrals of Hyperbolic Functions
_
coshaxdx =
1
a
sinhax + C (105)
_
e
ax
coshbxdx =
_
¸
_
¸
_
e
ax
a
2
−b
2
[a coshbx −b sinhbx] + C a = b
e
2ax
4a
+
x
2
+ C a = b
(106)
_
sinhaxdx =
1
a
coshax + C (107)
_
e
ax
sinhbxdx =
_
¸
_
¸
_
e
ax
a
2
−b
2
[−b coshbx + a sinhbx] + C a = b
e
2ax
4a

x
2
+ C a = b
(108)
_
e
ax
tanhbxdx =
_
¸
¸
¸
¸
¸
_
¸
¸
¸
¸
¸
_
e
(a+2b)x
(a + 2b)
2
F
1
_
1 +
a
2b
, 1, 2 +
a
2b
, −e
2bx
_

1
a
e
ax
2
F
1
_
a
2b
, 1, 1E, −e
2bx
_
+ C a = b
e
ax
−2 tan
−1
[e
ax
]
a
+ C a = b
(109)
_
tanhbxdx =
1
a
lncoshax + C (110)
_
cos axcoshbxdx =
1
a
2
+ b
2
[a sinaxcoshbx
+b cos axsinhbx] + C (111)
4
_
cos axsinhbxdx =
1
a
2
+ b
2
[b cos axcoshbx+
a sinaxsinhbx] + C (112)
_
sinaxcoshbxdx =
1
a
2
+ b
2
[−a cos axcoshbx+
b sinaxsinhbx] + C (113)
_
sinaxsinhbxdx =
1
a
2
+ b
2
[b coshbxsinax−
a cos axsinhbx] + C (114)
_
sinhaxcoshaxdx =
1
4a
[−2ax + sinh2ax] + C (115)
_
sinhaxcoshbxdx =
1
b
2
−a
2
[b coshbxsinhax
−a coshaxsinhbx] + C (116)
5

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->